Late Triassic freshwater conchostracan, ostracods, and stromatolites from Huai Hin Lat Formation, northeastern Thailand. - Chitnarin, Anisong; Kershaw, Stephen; Promduang, Anucha; Tepnarong, Prachya (Thai Geoscience Journal, 2022)
Although ostracods are well-known in marine environments, their study in non-marine facies is less understood. In the Khorat Plateau region of northeast Thailand, a well-exposed example of fluvial-lacustrine facies in the Dat Fa Member of the Huai Hin Lat Formation (Norian, Late Triassic), contains abundant ostracods that in the oldest known non-marine sedimentary sequence in Thailand. Euestheria buravasi, the Late Triassic index fossil is recovered for the first time at the studied section. Associated with the ostracods is a restricted non-marine stromatolite, together with non-marine clastic sediments. A combined study of ostracod faunas and sedimentary characters herein provides more detail of the nature of the environments of the Huai Hin Lat Formation. The ostracods are from the superfamily Darwinulidae, thus are a low diversity assemblage of exclusively non-marine forms that confirms the freshwater nature of the beds. The stromatolite layer consists of some stromatolite domes of hybrid construction combining laminae with filamentous structure (suspected to be cyanobacteria) together with probable inorganic layers of fine-grained carbonate. The stromatolite represents an episode of carbonate-rich waters available in these freshwater facies to create a hybrid stromatolite deposit in this non-marine setting. The sum of facies study in this investigation makes an interpretation of the setting as being very shallow water, in contrast to other studies that proposed the lacustrine setting was deeper.